Industrial Biotechnology : Plant Systems, Resources and Products - Kumar, Vikas; Sehrawat, Nirmala; Yadav, Mukesh (De Gruyter STEM, 2019)
Industrial Biotechnology summarizes different aspects of plant biotechnology such as using plants as sustainable resources, phytomedical applications, phytoremedation and genetic engineering of plant systems. These topics are discussed from an academic as well industrial perspective and thus highlight recent developments but also practical aspects of modern biotechnology.